Biologics During Pregnancy and Breastfeeding Among Women With Rheumatic Diseases: Safety Clinical Evidence on the Road - Beltagy, Asmaa; Aghamajidi, Azin; Trespidi, Laura; Ossola, Wally; Meroni, Pier Luigi (Frontiers in Pharmacology, 2021)
Females are generally more affected by autoimmune diseases, a fact that underlines the relationship with pregnancy and more precisely the safety of anti-rheumatic drugs in pregnancy and lactation. Biologic therapies are increasingly prescribed to treat and maintain remission in a significant number of systemic autoimmune rheumatic diseases. The experience with the use of biologics during gestation is extremely lacking because of the observational nature of the available studies and the difficulty in designing proper clinical trials in pregnancy. Among the studied biologics, more information was published on TNF inhibitors and in particular on their potential passage through the placenta and impact on the fetus. Currently, a Fab’ fragment of anti-TNF monoclonal IgG, certolizumab pegol, is considered safe with almost no placental transfer. Subsequent observations are suggesting a comparable safety for the soluble TNF receptor etanercept. Another biologic, eculizumab, the anti-C5a antibody used to treat complement-mediated microangiopathies, is also regarded as safe owing to the unique engineered IgG2/4κ formulation that limits its passage through the placental barrier. Still, long-term data about children born to women treated with biologics in pregnancy are not attainable. Data on breastfeeding are currently available for several biologics. In this article, we review the literature available so far concerning what is considered safe during pregnancy and lactation, what is not and what are the future prospects.